Exploring the association between volition and participation in daily life activities with older adults living in the community. (November 2014) - Pritchard, Elizabeth K; Brown, G Ted; Barker, Anna L; Haines, Terry P
Objective: To explore the association between volition and participation in daily activities with older adults living in the community. Design: Cross-sectional study. Setting: Community-dwelling, residing in Victoria (Australia). Participants: A total of 244 adults, of 70 years and older, drawn from a convenience sample, living in their own homes. Main measures: Individuals' participation in daily activities was obtained via phone interviews, from the completion of the Phone-FITT survey. Levels of volition (identified under three items; personal causation, values and interests) were collected using the Volition Scale. Analyses were completed through linear regression. Results: The participants' mean age was 77.5 years (SD 5.7) with 60% being female. Higher levels of participation were associated with higher levels of volition in light housework ( n = 225, p = 0.008), shopping ( n = 239, p = 0.018), lifting weights to strengthen legs ( n = 23, p = 0.031), walking for exercise ( n = 163, p < 0.001) and gardening ( n = 183, p = 0.001). Conclusions: Increased volition is associated with increased participation in physical activities with community-dwelling older adults.